Contribution of common deletion to total deletion burden in mitochondrial DNA from inner ear of d-galactose-induced aging rats - Zhong, Yi; Hu, Yu-Juan; Yang, Yang; Peng, Wei; Sun, Yu; Chen, Bei; Huang, Xiang; Kong, Wei-Jia (Mutation research, 2011)
Mitochondrial DNA (mtDNA) mutations, especially deletions, have been suggested to play an important role in aging and degenerative diseases. In particular, the common deletion in humans and rats (4977bp and 4834bp deletion, respectively) has been shown to accumulate with age in post-mitotic tissues with high energetic demands. Among numerous deletions, the common deletion has been proposed to serve as a molecular marker for aging and play a critical role in presbyacusis. However, so far no previous publication has quantified the contribution of common deletion to the total burden of mtDNA deletions in tissues during aging process. In the present study, we established a rat model with various degrees of aging in inner ear induced by three different doses of d-galactose (d-gal) administration. Firstly, multiple mtDNA deletions in inner ear were detected by nested PCR and long range PCR. In addition to the common deletion, three novel mtDNA deletions were identified. All four deletions, located in the major arc of mtDNA, are flanked by direct repeats and involve the cytochrome c oxidase (COX) subunit III gene, encoded by mtDNA. Additionally, absolute quantitative real-time PCR assay was used to detect the level of common deletion and total deletion burden of mtDNA. The quantitative data show that the common deletion is the most frequent type of mtDNA deletions, exceeding 67.86% of the total deletion burden. Finally, increased mtDNA copy number, reduced COX activity and mosaic ultrastructural impairments in inner ear were identified in d-gal-induced aging rats. The increase of mtDNA replication may contribute to the accelerated accumulation of mtDNA deletions, which may result in impairment of mitochondrial function in inner ear. Taken together, these findings suggest that the common deletion may serve as an ideal molecular marker to assess the mtDNA damage in inner ear during aging.